Effects of replacing maize meal with rumen filtrate-fermented cassava meal on growth and egg production performance in Japanese quails (Cortunix japonica) - Kanyinji, Francisco; Moonga, Mathews (Journal of Advanced Veterinary and Animal Research, 2014)
This study was conducted to evaluate the effects of replacing maize in quail diets with graded levels of rumen filtrate-fermented cassava meal (FCM) on growth and egg production performances. Cassava meal (CM) was mixed with dried manure of layer at 75 g/kg CM, which was mixed with freshly collected rumen filtrate (at 1 L/5 kg CM), and finally fermented in sealed bags for 14 days. It was then sun-dried and added in grower or finisher diets at 0, 50, 75 and 100%. Then, 84 three weeks-old Japanese quails (Cortunix japonica) were divided into four equal groups; the birds were randomly assigned to 0, 50, 75 and 100% FCM grower/layers diets, and were reared until 56 days of age. Daily feed consumption, weekly body weights, weight gains, feed conversion ratios (FCR), hen-day, and egg weights were monitored. The quails fed with 75% FCM were found to be superior (p<0.05) for body weight, feed intake, weight gain, and egg weights. However, birds fed control diets had higher (p<0.05) hen-day, but lower (p<0.05) in egg weights. Complete replacement of maize with FCM (100%) had similar (p>0.05) effect on feed intake, body weight, and weight gain, as compared to those of fed control diets. Thus, replacing maize with FCM had no deleterious effects on growth performance, but depressed hen-day. However, better growth performance was obtained when maize was replaced at 75% FCM. DOI: http://dx.doi.org/10.5455/javar.2014.a19 J. Adv. Vet. Anim. Res., 1(3): 100-106, September 2014